Large scale MP2 calculations with fragment molecular orbital scheme - Mochizuki, Yuji; Koikegami, Shigeru; Nakano, Tatsuya; Amari, Shinji; Kitaura, Kazuo (Chemical physics letters, 2004)
We have recently developed a parallelized integral-direct algorithm for the second-order Møller–Plesset perturbation theory (MP2) and implemented it into the ABINIT-MP program of the fragment molecular orbital (FMO) scheme. A flexible parallelization is possible by combining the fragment indices (upper level) and the two-electron integral indices (lower level) on distributed computational resources, leading to an enhancement of in-core processings. In this Letter, we carry out a series of benchmark FMO–MP2 calculations of realistic proteins consisting of the tens of thousands of basis functions. The performance is shown to be high, indicating that the ABINIT-MP program is easily applicable to the realistic systems.